Activity of Russian Entrepreneurs in Field of Tea Production in Yangtze River Valley in Second Half of 19th Century - I. R. Khamzin; R. T. Ganiev; A. V. Kochnev (Научный диалог, 2022)
The development of the Russian tea industry in the Chinese provinces along the Yangtze River valley in the second half of the 19th century is examined in the article. It is noted that among the regions where Russian tea factories were located, the main role belonged to the province of Hubei, in addition, the presence of production in the provinces of Hunan and Jiangxi was revealed. The historical situation in which the Russian tea industry arose is studied. Based on archival and published material, the number of Russian factories in Central China is shown. It is revealed that in the 70s of the 19th century, Russian trading houses operating in China began to transfer factories from the interior of Hubei province to the port of Hankou. It has been determined that cheap brick tea has become the main commodity produced in Russian factories, while Russian entrepreneurs are gradually abandoning the production of long leaf tea. Separately, the features of tea production and the organization of the workflow were studied. It is proved that the Russian tea factory in China has become one of the important factors of not only economic, but also socio-cultural contact between Russian and Chinese civilizations.